KEHIDUPAN STRAIGHT EDGE MUSIK HARDCORE PADA LINGKUP MASYARAKAT - Luthfan Pradyansyah; Teguh Wijaya Mulya; Siti Yunia Mazdafiah (Perpustakaan Universitas Surabaya, 2021)
Abstract— Hardcore becomes an interesting sub culture by many people with various negative perceptions both in terms of style and deviant behavior. Even worse, due to the negative stereotypes, the Hardcore followers become victims of violence because they are considered disturbing. Straight Edge is the lifestyle, philosophy, and movement of youth in the Hardcore music environment that adheres to clean living style. The Straight Edges contrary with how groups affect individuals. The purpose of this study is to describe the factors that make someone love Hardcore music, the impact of Hardcore music on the life of the Straight Edges, the response of the Straight Edges in responding to the negative stereotypes, and the factors that forming the Straight Edges lifestyle This research has taken used a qualitative approach through the phenomenological method. In this study, researcher used interview techniques with three informants who were divided into three types that is musicians, fans, and activists of Hardcore music programs that are Straight Edge. The results of this study indicate the factors that appeal to Hardcore music, that is: (1) beat that tends to be up–beat, (2) giving